Design, Implementation and Community Impact of QLattes: An Open Source Browser Extension for Qualis Annotation and Visualization in the Lattes Platform - Mendonça, Nabor C.; Rodrigues, Maria Andréia Formico; Mendonça, Lucas R. (Journal of the Brazilian Computer Society, 2026)
QLattes is an open-source browser extension for Chrome and Firefox that assists researchers and administrative academic staff by automatically classifying and annotating journal publications listed on Brazil’s Lattes CV platform, using CAPES’ former Qualis ranking system. The tool also provides features for filtering, analyzing, and visualizing this publication data. This article presents QLattes’s architecture and implementation, alongside a large-scale analysis of usage data from Google Analytics and an online survey of 1,495 anonymous participants. Usage data show QLattes reached over 27,000 weekly active users as of October 2025 across all five regions of Brazil as well as many other countries. The survey analysis moves beyond aggregate metrics—which confirm high user satisfaction—to present a detailed cross-sectional analysis. We reveal several insights, including that (1) high-frequency "power users’’ have a distinct behavioral profile focused on administrative and evaluative tasks, not just self-assessment, and (2) feature request priorities, such as support for conference papers, vary significantly by user occupation and geographic region. These numbers offer concrete evidence of the tool’s extensive reach and impact within the Brazilian academic community during the Qualis era. QLattes’s modular architecture also allows easy extension to support additional publication types and metrics beyond Qualis, ensuring its continued relevance in Brazil’s evolving research evaluation landscape. The tool’s source code is freely available at https://github.com/nabormendonca/qlattes.